RELIGION AND GREEN: THE DUAL POWER OF ESG AND SHARIAH-COMPLIANT STOCKS IN BRAND VALUES OF MALAYSIA, INDONESIA, AND SAUDI ARABIA - Loang, Ooi Kok; Candra, Sevenpri (Journal of Islamic Monetary Economics and Finance, 2025)
This study examines the differential impact of Environmental, Social, and Governance (ESG) factors and Shariah compliance on brand value and stock returns across Malaysia, Indonesia, and Saudi Arabia using a sample of 1,474 publicly listed Shariah-compliant firms. Using panel data regression, quantile-on-quantile regression, Granger causality, and FGLS methods, we find that ESG factors significantly enhance brand value and stock returns in Malaysia and Indonesia, with stronger effects than conventional stocks, especially under positive investor sentiment. However, in Saudi Arabia, ESG factors are insignificant, and Shariah compliance alone drives financial performance, indicating that alignment with Islamic principles is a prerequisite for market impact in this context. The quantile-on-quantile analysis further shows that ESG and Shariah compliance yield stronger effects at higher quantiles of brand value, benefiting firms with greater brand equity. These results validate the signaling theory, highlighting ESG and Shariah compliance as mechanisms to reduce information asymmetry and enhance investor confidence in Islamic financial markets. For policymakers, this study underscores the need for robust ESG and Shariah compliance standards, advocating transparent reporting to foster market trust and attract sustainable investment, particularly by advancing a Shariah-compliant green economy in Saudi Arabia and beyond.